The Effect of Screen Time on Learning Concentration of Children Aged 5–6 Years in Jatireja Village, East Cikarang District - Fadila Bella Anggraeni Purwandi; Ine Nirmala; Nur Rochimah (S&Co Publishing, 2026)
The rapid development of digital technology has influenced children's daily activities, including learning and playing patterns. Digital devices such as smartphones, tablets, and televisions are increasingly accessible to early childhood children. Although digital media can provide educational benefits, excessive screen exposure may negatively affect children's cognitive development, especially their ability to maintain attention during learning activities. This study aimed to analyze the effect of screen time on the learning concentration of children aged 5–6 years in Jatireja Village, East Cikarang District. This study used a quantitative approach with an ex post facto research design. The population consisted of 1,011 children aged 5–6 years from seven kindergartens. The sample consisted of 212 children selected through probability sampling using cluster sampling. Data were collected through observation, questionnaires, and parent surveys. Data analysis used descriptive statistics and simple linear regression. The results showed that screen time had a negative and significant effect on learning concentration with a regression coefficient of -0.382 and significance value of 0.002 (p < 0.05). Screen time contributed 4.4% to the variation in learning concentration. Therefore, appropriate regulation of digital device use is required.